Rethinking Distributed Ledger Technology. - Kuhn, Rick; Yaga, Dylan; Voas, Jeffrey (Computer (00189162), 2019)
Distributed ledger technology (DLT) offers new and unique advantages for information systems, but some of its features are not a good fit for many applications. We review the properties of DLT and show how two recently developed ideas can be used to retain its advantages while simplifying design.